Purifying and characterizing bacterially expressed soluble Lactate Dehydrogenase from Plasmodium knowlesi for the development of anti-malarial drugs - Ogu Salim, Nurhainis; Ahmad Fuad, Fazia Adyani; Khairuddin, Farahayu; Wan Seman, Wan Mohd Khairulikhsan; Jonet, Mohd Anuar (MDPI, 2021)
Plasmodium lactate dehydrogenase (pLH) is one of the enzymes in glycolysis with potential target for chemotherapy. This study aimed to clone, overexpress and characterize soluble recombinant lactate dehydrogenase from Plasmodium knowlesi in a bacterial system. Synthetic P. knowlesi lactate dehydrogenase (Pk-LDH) gene was cloned into pET21a expression vector, transformed into Escherichia coli strain BL21 (DE3) expression system and then incubated for 18 h, 20 °C with the presence of 0.5 mM isopropyl β-d-thiogalactoside in Terrific broth supplemented with Magnesium sulfate, followed by protein purifications using Immobilized Metal Ion Affinity Chromatography and size exclusion chromatography (SEC). Enzymatic assay was conducted to determine the activity of the enzyme. SDS-PAGE analysis revealed that protein of 34 kDa size was present in the soluble fraction. In SEC, a single peak corresponding to the size of Pk-LDH protein was observed, indicating that the protein has been successfully purified. From MALDI-TOF analysis findings, a peptide score of 282 was established, which is significant for lactate dehydrogenase from P. knowlesi revealed via MASCOT analysis. Secondary structure analysis of CD spectra indicated 79.4% α helix and 1.37% β strand structure. Specific activity of recombinant Pk-LDH was found to be 475.6 U/mg, confirming the presence of active protein. Soluble Pk-LDH that is biologically active was produced, which can be used further in other malaria studies.